Aquinas and Solovyov: Unified Christian ontological-epistemology in critique of epistemic reductivism - Scott, Callum David (Verbum et ecclesia, 2018)
Modern positivism reduced 'being to knowing', considering being as cognitively inaccessible and its study as meaningless. In recent 'scientistic' scholarship, these presuppositions have found new life. However, Christian ontologically founded epistemology is concerned by this dismissal of being. In search of an ecumenical response, this work attempts a multi-patrimonial Christian, philosophical counterargument to reductive anti-metaphysical epistemology. A comparative analysis between the ontological epistemologies of Saint Thomas Aquinas (as representative of the Mediaeval Occidental Christian tradition) and Vladimir Solovyov (a modern, eastern Christian philosopher-theologian) is made. In this contrast, it is argued that a harmonic Christian philosophical voice is evident. In both Western and Eastern approaches, the causal complexity of being - by the fact that being is - implores the philosopher for a unified account, in contradiction to anti-metaphysical reductivism in any of its forms.Intradisciplinary and/or interdisciplinary implications: Bringing the Christian metaphysics and epistemology of Aquinas and Solovyov into conversation, which the author has not seen done in other literature, this work brings together Epistemology and Metaphysics, leading to a unified practical application in the critique of issue within contemporary Philosophy of Science, scientism.